Design analysis of an implant and antenna system by using Taguchi method - Celik, Nevin; Turgut, Emre; Bayazit, Yilmaz (Springer, 2018)
In present study, to investigate the thermal effects of the rechargeable neuromodulation implants (an implant and antenna together) in the body, a numerical analysis is performed by using commercial software ANSYS. Since it is well established that both the antenna and the implant generate heat, both of these heat sources may increase the tissue temperature in the subcutaneous zone and may also increase the temperature in the deeper tissue. Therefore, the sizes and heat generation amounts of the implant-antenna system gain great importance and a parametric evaluation that shows the effects of the design parameters on the temperature becomes necessary. For this aim, an optimization study is performed. The runs of the numerical simulations are determined by well-known design analysis method, namely Taguchi and the parametric evaluation of the study is carried out by Analysis of Variance (ANOVA) method. The design parameters considered are; (i) heat generated by the antenna q (a) (50, 52 and 54 W/m(2)), (ii) heat generated by the implant q (i) (30 and 35 W/m(2)), (iii) thickness of the implant t (i) (9, 11, and 13 mm) and finally (iv) the radius of the antenna R (a) (31, 35, 39 mm). The results showed that higher antenna radii result in higher temperatures in the tissue, whilst the least effective design parameter on the temperature is the heat generation of the implant.
Keywords: Thermal-Properties; Bioheat Transfer; Skin; Temperature